1998
DOI: 10.4315/0362-028x-61.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 during the Manufacture of Pepperoni

Abstract: This study investigated the growth and survival of Escherichia coli O157:H7 during the manufacture of pepperoni to determine whether a 5-log10-unit decline in numbers, as recommended by the U.S. Food Safety and Inspection Service (FSIS), could be achieved. A range of pepperoni formulations with variations in salt (2.5 to 4.8%) and sodium nitrite (100 to 400 ppm) levels, and with pH (4.4 to 5.6) adjusted by manipulation of dextrose concentrations were prepared. The batters produced were inoculated with E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In many of the studies included in this meta-analysis, it was observed that lower levels of pH (4-7, 11, 14, 49) and a w (49,57) are associated with greater reductions in E. coli in fermented meats. However, from our analyses of the collated data, while inactivation of E. coli ensues when environmental factors preclude growth, further decreases in pH or a w do not appear to greatly hasten inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In many of the studies included in this meta-analysis, it was observed that lower levels of pH (4-7, 11, 14, 49) and a w (49,57) are associated with greater reductions in E. coli in fermented meats. However, from our analyses of the collated data, while inactivation of E. coli ensues when environmental factors preclude growth, further decreases in pH or a w do not appear to greatly hasten inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the survival of E. coli O157:H7 cells in dried and fermented meat products (Hinkens et al, 1996;Faith, Parniere, Larson, Lorang, & Luchansky, 1997, 1998bFaith et al, 1998c;Riordan et al, 1998) have indicated that traditional fermentation processes, which do not include a thermal processing step, have not achieved a 5-log reduction of inoculated E. coli O157:H7 cells. Contaminated dried meats, such as jerky, may pose a potentially greater threat to consumers than fermented meats since jerky can easily be prepared at home with limited equipment and precision in methods used (Faith et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of products with several months long ripening periods, such inactivation ratio cannot be expected under typical, currently practiced fermentation and drying conditions and additional hurdles are required. It is known that traditional processes for manufacturing pepperoni served to provide only 2-log reduction in E. coli O157:H7 (Faith, Parniere, Larson, Lorang, & Luchansky, 1997;Riordan et al, 1998). Normanno et al (2002) found that E. coli O157:H7 declined four log cycles in some inoculated short ripened Italian fermented sausage.…”
Section: Introductionmentioning
confidence: 97%